(-3n+(-6))-(-5n+2)=

Simple and best practice solution for (-3n+(-6))-(-5n+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3n+(-6))-(-5n+2)= equation:


Simplifying
(-3n + (-6)) + -1(-5n + 2) = 0
(-3n + -6) + -1(-5n + 2) = 0

Reorder the terms:
(-6 + -3n) + -1(-5n + 2) = 0

Remove parenthesis around (-6 + -3n)
-6 + -3n + -1(-5n + 2) = 0

Reorder the terms:
-6 + -3n + -1(2 + -5n) = 0
-6 + -3n + (2 * -1 + -5n * -1) = 0
-6 + -3n + (-2 + 5n) = 0

Reorder the terms:
-6 + -2 + -3n + 5n = 0

Combine like terms: -6 + -2 = -8
-8 + -3n + 5n = 0

Combine like terms: -3n + 5n = 2n
-8 + 2n = 0

Solving
-8 + 2n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2n = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 2n = 0 + 8
2n = 0 + 8

Combine like terms: 0 + 8 = 8
2n = 8

Divide each side by '2'.
n = 4

Simplifying
n = 4

See similar equations:

| 5(3)=10y+20 | | 16(-10-19y)+15y= | | 8-4+8= | | 2(+4)+6=22 | | 31x+115=84 | | -4x-44+x=31 | | 8(x-8)-2(x-1)+5x= | | x-4+8=12 | | -7c-5=c-373 | | -3y-12=-9(3) | | -x-10x-76=89 | | 2x+x=6.30 | | -6t+20=4t-20-5t | | 2+2b+bh+1h=a | | -x^2+254x=0 | | -116+12x-x=38 | | 310+n=200 | | 20x-300x^2=0 | | 48=15 | | 12y+36=4(9+3y) | | 1(3-x)=10(3-2x) | | x+2.7=5.6 | | 8h+4=h-311 | | 6x^2-12x+18=3x^2-15 | | 3+log[4](-2X)=4 | | 6x+36y=42 | | 12(18f+10)= | | -.33m-4=10 | | j+298=-9j+8 | | -3(9-(-3))+5= | | r(5r-4)=0 | | X+(x+2)+(x+4)=4x-17 |

Equations solver categories